1988
DOI: 10.1177/0310057x8801600403
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Alfentanil Requirements in European and Asian Patients during General Anaesthesia

Abstract: Alfentanil requirements were compared in thirty-six Asian and forty-three European patients during general anaesthesia with muscle relaxants. Alfentanil infusion at 5 jlg/kg/min was started immediately after induction with thiopentone and alcuronium. The infusion rate was reduced to 0.5 jlg/kg/min after ten minutes. An incremental dose of5 jlg/kg/minfor five minutes was given on each occasion when anaesthesia was clinically judged to be inadequate. Recovery parameters were recorded. Pharmacokinetics were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 18 publications
(6 reference statements)
1
14
0
Order By: Relevance
“…[23][24][25] Houghton et al 25,26 concluded that ethnicity affected recovery from suxamethonium and from anesthesia, with Europeans recovering faster than Asians. The same authors also found that although the elimination half-life of alfentanil in Chinese and Nepalese patients were both significantly shorter than that of Europeans, mean plasma concentrations did not differ significantly at the time of recovery of spontaneous ventilation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[23][24][25] Houghton et al 25,26 concluded that ethnicity affected recovery from suxamethonium and from anesthesia, with Europeans recovering faster than Asians. The same authors also found that although the elimination half-life of alfentanil in Chinese and Nepalese patients were both significantly shorter than that of Europeans, mean plasma concentrations did not differ significantly at the time of recovery of spontaneous ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…The same authors also found that although the elimination half-life of alfentanil in Chinese and Nepalese patients were both significantly shorter than that of Europeans, mean plasma concentrations did not differ significantly at the time of recovery of spontaneous ventilation. 23 A study of postoperative morphine consumption revealed that there were significant differences in the dose of analgesics administered to black, Hispanic, and white patients. 27 Other studies, though, did not identify ethnic differences in the sensitivity to analgesics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The slower recovery of the Asians from anaesthesia is difficult to explain but it supports the work of Aun and colleagues [21] who found slower recovery from anaesthesia in Asians given alfentanil by infusion as a supplement to nitrous oxide and muscle relaxant anaesthesia and also that of Houghton and colleagues [22] who found greater sedation in Asians following pethidine analgesia after upper abdominal surgery.…”
Section: Discussionmentioning
confidence: 53%
“…It is also commonly believed that Asians are more reluctant to report pain and have a greater fear of opioids than Caucasians. [5][6][7] Despite these assertions, few studies have evaluated the influence of ethnicity on postoperative pain. [2][3][4][5] Our group have recently reported findings from a prospective cohort comparing opioid requirement and postoperative pain in a matched group of 136 Chinese patients from Hong Kong and Caucasian patients in Melbourne who received major surgery.…”
Section: Résumémentioning
confidence: 99%